Problems of Parliamentary Oversight on Secret Activities of Institutes of National Security Assurance System of Georgia - Alapishvili, Levan (Journal of Law, 2023)
Democratic governance is based on the accountability of the government to the parliament. Oversight of the government activities by the representative body that has absolute legitimation of population ensures democratic environment for decision-making and efficient accountability of the Government. An effective system of accountability of the government to the parliament ensures the accountability of the government to its population. Parliamentary oversight of the government's activities is a constitutional obligation to ensure accountability to the source of power, i.e. citizens. Significant part of activities and decisions of government is related to secret activities and documents. Legislative regulation of state secrets and delegation of authority or authorization to the Government is an exclusive competence of Parliament under the Constitution of Georgia. The Parliament, the members of which do not have access to state secrecy cannot ensure the parliamentary oversight of secret activity of the Government or if decision-making regarding the issue of allowing access of Members of Parliament to the state secrecy is delegated to the government. Unlimited delegation of the right to regulate the access of MPs to the state secrecy comes into conflict with the Constitution, because it means the violation of accountability to the Parliament and separation of power which deprives the Parliament of the possibility to exercise oversight on the Government’s work. This work provides an analysis of the regulatory environment for state secrecy of Georgia and the delegation of authority of legal regulation of state secret management. By presenting a comparative analysis of Georgian and foreign practice of parliamentary oversight regarding state secret activities, we are putting forward for discussion the issues related to the regulation of accessibility to state secrecy by members of Parliament and the suggestions regarding the solution of actual issues of parliamentary oversight of government’s secret activities.